Function | Derivative | ||||
---|---|---|---|---|---|
\sin(x) | \cos(x) | ||||
\cos(x) | -\sin(x) | ||||
\tan(x) | \sec2(x) | ||||
\cot(x) | -\csc2(x) | ||||
\sec(x) | \sec(x)\tan(x) | ||||
\csc(x) | -\csc(x)\cot(x) | ||||
\arcsin(x) |
| ||||
\arccos(x) |
| ||||
\arctan(x) |
| ||||
\arccot(x) |
| ||||
\arcsec(x) |
| ||||
\arccsc(x) |
|
All derivatives of circular trigonometric functions can be found from those of sin(x) and cos(x) by means of the quotient rule applied to functions such as tan(x) = sin(x)/cos(x). Knowing these derivatives, the derivatives of the inverse trigonometric functions are found using implicit differentiation.
The diagram at right shows a circle with centre O and radius r = 1. Let two radii OA and OB make an arc of θ radians. Since we are considering the limit as θ tends to zero, we may assume θ is a small positive number, say 0 < θ < π in the first quadrant.
In the diagram, let R1 be the triangle OAB, R2 the circular sector OAB, and R3 the triangle OAC.
The area of triangle OAB is:
Area(R1 ) =\tfrac{1}{2} |OA| |OB|\sin\theta=\tfrac{1}{2}\sin\theta.
The area of the circular sector OAB is:
Area(R2)=\tfrac{1}{2}\theta.
The area of the triangle OAC is given by:
Area(R3 ) =\tfrac{1}{2} |OA| |AC|=\tfrac{1}{2}\tan\theta.
Since each region is contained in the next, one has:
Area(R1)<Area(R2)<Area(R3)\implies\tfrac{1}{2}\sin\theta<\tfrac{1}{2}\theta<\tfrac{1}{2}\tan\theta.
Moreover, since in the first quadrant, we may divide through by, giving:
1<
\theta | |
\sin\theta |
<
1 | |
\cos\theta |
\implies1>
\sin\theta | |
\theta |
>\cos\theta.
In the last step we took the reciprocals of the three positive terms, reversing the inequities.
We conclude that for 0 < θ < π, the quantity is always less than 1 and always greater than cos(θ). Thus, as θ gets closer to 0, is "squeezed" between a ceiling at height 1 and a floor at height, which rises towards 1; hence sin(θ)/θ must tend to 1 as θ tends to 0 from the positive side:
For the case where θ is a small negative number – π < θ < 0, we use the fact that sine is an odd function:
\lim \theta\to0+
\sin\theta \theta =1.
\lim | |
\theta\to0- |
\sin\theta | |
\theta |
= \lim | |
\theta\to0+ |
\sin(-\theta) | |
-\theta |
= \lim | |
\theta\to0+ |
-\sin\theta | |
-\theta |
= \lim | |
\theta\to0+ |
\sin\theta | |
\theta |
= 1.
The last section enables us to calculate this new limit relatively easily. This is done by employing a simple trick. In this calculation, the sign of θ is unimportant.
\lim\theta
\cos\theta-1 | |
\theta |
= \lim\theta\left(
\cos\theta-1 | |
\theta |
\right)\left(
\cos\theta+1 | |
\cos\theta+1 |
\right) = \lim\theta
\cos2\theta-1 | |
\theta(\cos\theta+1) |
.
Using the fact that the limit of a product is the product of limits, and the limit result from the previous section, we find that:
\lim\theta
\cos\theta-1 | |
\theta |
= \lim\theta
-\sin2\theta | |
\theta(\cos\theta+1) |
= \left(-\lim\theta
\sin\theta | |
\theta |
\right)\left(\lim\theta
\sin\theta | |
\cos\theta+1 |
\right) = (-1)\left(
0 | |
2 |
\right)=0.
Using the limit for the sine function, the fact that the tangent function is odd, and the fact that the limit of a product is the product of limits, we find:
\lim\theta\to
\tan\theta | |
\theta |
= \left(\lim\theta\to
\sin\theta | |
\theta |
\right) \left(\lim\theta\to
1 | |
\cos\theta |
\right) = (1)(1) = 1.
We calculate the derivative of the sine function from the limit definition:
\operatorname{d | |
Using the angle addition formula, we have:
\operatorname{d | |
\operatorname{d | |
We again calculate the derivative of the cosine function from the limit definition:
\operatorname{d | |
Using the angle addition formula, we have:
\operatorname{d | |
\operatorname{d | |
To compute the derivative of the cosine function from the chain rule, first observe the following three facts:
\cos\theta=\sin\left(\tfrac{\pi}{2}-\theta\right)
\sin\theta=\cos\left(\tfrac{\pi}{2}-\theta\right)
\tfrac{\operatorname{d}}{\operatorname{d}\theta}\sin\theta=\cos\theta
\tfrac{\operatorname{d}}{\operatorname{d}\theta}\cos\theta=\tfrac{\operatorname{d}}{\operatorname{d}\theta}\sin\left(\tfrac{\pi}{2}-\theta\right)
f(x)=\sinx, g(\theta)=\tfrac{\pi}{2}-\theta
\tfrac{\operatorname{d}}{\operatorname{d}\theta}f\left(g\left(\theta\right)\right)=f\prime\left(g\left(\theta\right)\right) ⋅ g\prime\left(\theta\right)=\cos\left(\tfrac{\pi}{2}-\theta\right) ⋅ (0-1)=-\sin\theta
Therefore, we have proven that
\tfrac{\operatorname{d}}{\operatorname{d}\theta}\cos\theta=-\sin\theta
To calculate the derivative of the tangent function tan θ, we use first principles. By definition:
\operatorname{d | |
\operatorname{d | |
\operatorname{d | |
\operatorname{d | |
\operatorname{d | |
One can also compute the derivative of the tangent function using the quotient rule.
\operatorname{d | |
1 | |
\cos2\theta |
=\sec2\theta
\operatorname{d | |
The following derivatives are found by setting a variable y equal to the inverse trigonometric function that we wish to take the derivative of. Using implicit differentiation and then solving for dy/dx, the derivative of the inverse function is found in terms of y. To convert dy/dx back into being in terms of x, we can draw a reference triangle on the unit circle, letting θ be y. Using the Pythagorean theorem and the definition of the regular trigonometric functions, we can finally express dy/dx in terms of x.
We let
y=\arcsinx
Where
- | \pi |
2 |
\ley\le
\pi | |
2 |
Then
\siny=x
Taking the derivative with respect to
x
{d\overdx}\siny={d\overdx}x
\cosy ⋅ {dy\overdx}=1
Substituting
\cosy=\sqrt{1-\sin2y}
\sqrt{1-\sin2y} ⋅ {dy\overdx}=1
Substituting
x=\siny
\sqrt{1-x2} ⋅ {dy\overdx}=1
{dy\overdx}=
1 | |
\sqrt{1-x2 |
We let
y=\arccosx
Where
0\ley\le\pi
Then
\cosy=x
Taking the derivative with respect to
x
{d\overdx}\cosy={d\overdx}x
-\siny ⋅ {dy\overdx}=1
Substituting
\siny=\sqrt{1-\cos2y}
-\sqrt{1-\cos2y} ⋅ {dy\overdx}=1
Substituting
x=\cosy
-\sqrt{1-x2} ⋅ {dy\overdx}=1
{dy\overdx}=-
1 | |
\sqrt{1-x2 |
Alternatively, once the derivative of
\arcsinx
\arccosx
\arcsinx+\arccosx=\pi/2
(\arccosx)'=-(\arcsinx)'
We let
y=\arctanx
Where
- | \pi |
2 |
<y<
\pi | |
2 |
Then
\tany=x
Taking the derivative with respect to
x
{d\overdx}\tany={d\overdx}x
Left side:
{d\overdx}\tany =\sec2y ⋅ {dy\overdx} =(1+\tan2y){dy\overdx}
Right side:
{d\overdx}x=1
Therefore,
(1+\tan2y){dy\overdx}=1
Substituting
x=\tany
(1+x2){dy\overdx}=1
{dy\overdx}=
1 | |
1+x2 |
We let
y=\arccotx
where
0<y<\pi
\coty=x
Taking the derivative with respect to
x
d | |
dx |
\coty=
d | |
dx |
x
Left side:
{d\overdx}\coty =-\csc2y ⋅ {dy\overdx} =-(1+\cot2y){dy\overdx}
Right side:
{d\overdx}x=1
Therefore,
| ||||
-(1+\cot |
=1
Substituting
x=\coty
| ||||
-(1+x |
=1
dy | =- | |
dx |
1 | |
1+x2 |
\arctanx
\arctanx+\arccotx=\dfrac{\pi}{2}
Let
y=\arcsecx \mid|x|\geq1
Then
x=\secy\mid y\in\left[0,
\pi | |
2 |
\right)\cup\left(
\pi | |
2 |
,\pi\right]
dx | |
dy |
=\secy\tany=|x|\sqrt{x2-1}
\sqrt{x2-1}
dy | |
dx |
=
1 | |
|x|\sqrt{x2-1 |
Alternatively, the derivative of arcsecant may be derived from the derivative of arccosine using the chain rule.
Let
y=\arcsecx=\arccos\left(
1 | |
x |
\right)
Where
|x|\geq1
y\in\left[0,
\pi | |
2 |
\right)\cup\left(
\pi | |
2 |
,\pi\right]
Then, applying the chain rule to
\arccos\left(
1 | |
x |
\right)
dy | |
dx |
=-
1 | ||||
|
\sqrt |
Let
y=\arccscx \mid|x|\geq1
Then
x=\cscy \mid y\in\left[-
\pi | |
2 |
,0\right)\cup\left(0,
\pi | |
2 |
\right]
dx | |
dy |
=-\cscy\coty=-|x|\sqrt{x2-1}
\sqrt{x2-1}
dy | |
dx |
=
-1 | |
|x|\sqrt{x2-1 |
Alternatively, the derivative of arccosecant may be derived from the derivative of arcsine using the chain rule.
Let
y=\arccscx=\arcsin\left(
1 | |
x |
\right)
Where
|x|\geq1
y\in\left[-
\pi | |
2 |
,0\right)\cup\left(0,
\pi | |
2 |
\right]
Then, applying the chain rule to
\arcsin\left(
1 | |
x |
\right)
dy | = | |
dx |
1 | ||||
|
\sqrt |